Movement of Particles in the Air - Csizmazia, Zoltán; Nagyné Polyák, Ilona (Acta Agraria Debreceniensis, 2001)
The physical characteristics of particles (seeds and fertilisers) can strongly influence their movements both in seeding and spreading machines and in the air. It is therefore essential to study these particles when constructing such machines. In this respect the size, shape, coefficient of friction and aerodynamic resistance of particles are of great importance. Due to their irregular shape, determining the size of particles is a troublesome process. A precise description of particles has to include several sizes and can be obtained from their screen size. Many physical properties of particles are relevant during movement in the air, but the aerodynamic resistance coefficient is the most important (Hofstee et al., 1990). Two types of wheat and four types of fertiliser particles were investigated (supported by the National Scientific Foundation OTKA, T-026482). An elutriator was designed and constructed (Csizmazia et al., 2000), in which an airflow is supplied by a centrifugal fan. Air velocity was measured with a thermal sensor. Particle sizes, mass and terminal air velocity were measured. The influence of the aerodynamic resistance coefficient on the particles’ motion is also discussed.